INDUSTRIAL UNCAPITAL UNGIRDER FRAME STRUCTURE FOR RESIDENTIAL BUILDINGS (Збірник наукових праць Галузеве машинобудування будівництво, 2017)
Design features of uncapital ungirder frame structure of building are presented: thecomponent elements, the advantages and disadvantages, usage experience.Problem of affordable housing in Ukraine, which is relevant now successfully solved bythe implementation into construction uncapital ungirder frame structure of building.The frame consists of the smallest number of precast concrete structures sizes, which aremanufactured at plants.The component elements of the system that have been tested in the laboratory of thedepartment of reinforced concrete and masonry structures and strength of materials PoltavaNational Technical Yuri Kondratyuk University are presented. The examples of buildings,which constructed on this constructive system in Poltava are provided.Keywords: Uncapital Ungirder Frame Structure, constructive system, affordablehousing.